Examining the emotional impact of sarcasm using a virtual environment - Pickering, Bethany; Thompson, Dominic; Filik, Ruth (Taylor & Francis, 2018)
This study aimed to investigate the emotional impact of sarcasm. Previous research in this area has mainly required participants to answer questions based on written materials, and results have been mixed. With the aim of instead examining the emotional impact of sarcasm when used in a more conversational setting, the current study utilised animated video clips as stimuli. In each clip, one individual answered general knowledge questions while the other provided feedback that could be delivered either literally or sarcastically, and either complimented or criticised the question answerer’s performance. Participants rated the feedback based on (1) the anticipated emotional impact on the recipient, (2) how the speaker intended the recipient to feel, and (3) whether the speaker intended to be humorous. Results overall supported the Tinge Hypothesis (Dews & Winner, 1995), showing that sarcastic criticism was rated as less negative than literal criticism, and sarcastic compliments (also termed “ironic praise”) were rated as less positive than literal compliments, when judged from both the perspective of the recipient and of the speaker. The speaker was also perceived to be intending to be more humorous when sarcastic feedback was given.